Individual Educative Plan for pupils with Special Educative Needs - Chichevska Jovanova, Natasha; Dimitrova Radojichikj, Daniela (Faculty of Philosophy, Skopje, 2013)
An individual educative plan (IEP) is a school document which enables adjustment of the school-educative process to the pupil with special educative needs. It is a developmental document, in which according to the actual operational level of pupils’ functioning there are set short-term and long-term goals, there are plans for its realization, monitoring of the achievements, and according to the results there are made changes, additions, predicting new steps and etc. The IEP prepares and realizes team, with clear definition of the tasks of each team member. The final goal of each IEP is to enable education of the pupil in the frames of its opportunities and capabilities, as well as to provide an atmosphere in the class, where the child will be accepted and satisfied. Unfortunately, our country still has not prepared rules for determination of the right of IEP, its application and evaluation; therefore there is not unification of these plans, on the national level. In this paper will be specified a model of IEP for pupils with special educative needs, included in the regular schools.
Индивидуален образовен план за ученици со посебни образовни потреби
Keywords: inclusive education, pupils with special educative needs, individual educative plan, teachers, expert coworkers, support